CEO narcissism and innovation ambidexterity: The moderating roles of CEO power and firm reputation. Issue 2 (13th December 2022) - You, Shuyang; Li, Zhengyu; Jia, Liangding; Cai, Yahua
Abstract: We examine how CEO narcissism affects firm innovation ambidexterity—the relatively balanced development in existing domains through exploitative innovation and in new domains through exploratory innovation. We theorize that firms led by more narcissistic CEOs are less likely to achieve innovation ambidexterity than those led by less narcissistic CEOs. Drawing on the trait activation theory, we further argue that this negative relationship is strongest when the CEO's power is intermediate and when the firm's reputation in the market is intermediate. Our analyses of a large‐scale onsite survey collected from 132 Chinese firms, matched with their archival patent information, support our hypotheses. Our study first sheds new light on the existing literature on the influence of firm managers on innovation ambidexterity by considering their different personalities. Second, this study contributes to the strategic leadership research on CEO narcissism by extending its implications to innovation ambidexterity as a new organizational outcome. Third, our study indicates that narcissistic CEOs' priority orders to chase the two conflicting needs—that is, the need to dominate decision‐making and the need for acclaim—vary in different scenarios. This finding thus challenges the assumption in prior CEO narcissism research that the behavioral manifestations of narcissistic personalities' different facets are the same regardless of the contextual scenarios.